What makes a non-professional video go viral: a case study of “I’m farming and I grow it” - Elliott, Lindsey (Kansas State University, 2013)
In 2013, creating a 57-second video can lead to more than $150,000 in profit for the creator and the creator can be anyone. This money-making opportunity comes from a recent popular trend known as a “viral video,” defined as a phenomenon of a video becoming highly popular through rapid, user-led distribution via the internet. However, research has not determined a clear model for creating a non-professional viral video. Interviews and YouTube analytics revealed how the video “I’m Farming and I Grow It,” a non-professional video created by three Kansas boys, was spread. Using the theories Uses and Gratifications and Two-Step Flow, this case study then analyzed the comments posted on the viral video and a content analysis of the comments identified the key factors mentioned by users, which contributed to the videos’ millions of views. The results conclude the key components for making a non-professional video go viral are “opinion leaders” spreading the message and video content that elicits positive feelings such as joy, humor, or praise. This study also provides a model to help a non-professional video go viral based on previous research and this case study.
Keywords: Viral video; Uses and gratifications theory; Two-step flow theory; YouTube; Media; Journalism (0391)